(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
People who are excluded from their communities frequently develop a low opinion of themselves and begin to blame themselves for the circumstances. They describe feeling completely unconcerned about the consequences of their actions and paying little attention to how others respond. Ostracism is best comprehended by first learning the numerous theories that inform it, which in turn lead to a new and different paradigm. Most workers have experienced some form of workplace incivility (WI), according to numerous studies; moreover, most workers reported experiencing multiple incidents of WI, whether verbal or nonverbal, and those who dealt with WI reported lower levels of productivity, happiness, and stress than those who did not. Employees and employers alike may view it as a time-consuming process. The results of the data analysis would show whether or not the variables in the study are significantly related to one another. It has always been challenging for businesses in the service industry to attract and retain skilled workers who can help them achieve their goals.